Pandemia COVID-19 jako czynnik weryfikujący funkcje państwa w gospodarce - Nizioł, Krystyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
The aim of the study is to show that the performance of specific functions by the state in the economy during crises is a guarantee of socio-economic stability. In the period of the COVID-19 pandemic, it was the state that was expected to apply various forms of intervention in the economy to counteract the effects of this situation. Such measures were taken by many countries, including Poland.
Keywords: functions of the state; COVID-19 pandemic